English Teachers’ Perceptions of the Role of Lesson Planning in Classroom Management - Alghamdy, Rashed Zannan (International Journal of Linguistics, 2023)
In the present article, the researcher aims to identify the relationship between lesson plans and classroom management and attempt to determine the effect of English teachers’ lesson preparation on the implementation of those lessons. Further, I seek to explore English teachers’ perceptions toward the role of lesson planning in classroom management in Saudi English as a first language (EFL) classroom. I collect data from 87 English teachers in secondary schools in Al-Baha City via electronic questionnaire, and the findings demonstrate the importance of lesson planning in classroom management, revealing that Saudi English teachers prepare their lessons effectively to sufficiently manage classrooms. In addition, the results indicate that lesson planning is an essential skill that English teachers must cultivate to create a successful classroom environment. Moreover, the outcomes of the present study highlight most Saudi English teachers’ attitudes toward the role of lesson planning in classroom management are positive. Finally, it indicates a significant and positive relationship between effective lesson preparation and teachers’ abilities to create a successful EFL classroom environment.